Difficultés des enseignants lors de l'enseignement de questions socialement vives : quelle conceptualisation pour mieux les comprendre ? - Amélie Lipp
Agricultural schools are particularly concerned by the introduction of socially acute questions (SAQ) into curricula. A great deal of research exists on the difficulties which teachers face in teaching SAQ. However, few studies clearly defined the notion of difficulty and have been based on situated approach. We consider that the concept of the reality of the activity developed in the clinic of activity provides elements of understanding of difficulties of teachers dealing with SAQ. In this article, we articulate the theoretical frameworks of the didactics of SAQ and of the clinic of activity in order to better understand the conflicts at work in teachers' activity. An intervention research conducted with animal husbandry teachers who teach the question of farm animal welfare shows that teachers' difficulties are inextricably linked to what the teachers give up doing or what they try without succeeding.